(untitled) (Journal of Governance and Development (JGD), 2023)
Political Violence has recently become a recurring decimal in Northern Nigeria especially in the North-Eastern part of the country where peace seems to have eluded the region since 2009. Several scholarly inputs were propounded in an attempt to address and find a lasting solution to the persistent incidence of violence ravaging the region. This article is another attempt geared toward addressing the problem by looking at it from a different perspective that is the youth Bulge Phenomenon. It is the conception of this paper that, the genesis, the life span and the demise of political violence is greatly influence by the socio-cultural and political environment surrounding it. To understand political violence and the factors that breed it, one has to understand the environment that actually nurtured it. In other words, without understanding the socio-political attributes of a given population, one will not understand the causes of insurgency within it. This paper views environment as a key factor in understanding the political violence within the context of the North-Eastern Nigeria. It examines environment from a demographic parlance and adopts the youth Bulge theory and the social identity theory to conceptually analyse the key elements that continue to shape and mould the growth of political violence in the North-Eastern Nigeria, where institutional weakness due to poor governance, social categorization and the formation of social network were discovered to be the contributing factors to the menace.